Differences in exercise behaviors by diabetes status: implications for Americans with type 1 diabetes - Beattie, Cassandra Maria (Kansas State University, 2019)
Background: In the United States, 9.4% of adults have type one or type two diabetes (T1D, T2D). Although Federal physical activity (PA) guidelines including aerobic and strength training exercises are recommended for T2D; guidelines are not provided for T1Ds. A better understanding of differences in PA behaviors between T1D and T2D populations is needed, along with comparisons to non-diabetic (ND) Americans. As a health behavior, PA is influenced by factors such as knowledge and beliefs, degree of self-regulation skills and abilities, and the degree of social facilitation, as captured in the Integrated Theory of Health Behavior Change (ITHBC). Purpose: This study compared PA behaviors of adults with T1D, T2D, and NDs as well as examined how their PA behaviors fit into the ITHBC framework (knowledge and beliefs, social facilitation, self-regulation skill and ability, engagement of self-management behavior, and health status). T1D were hypothesized to achieve more activity in average moderate and vigorous aerobic minutes per week and average days per week of strength training than T2D. Methods: Male (n=68) and female (n=267) participants ages 18-64 were recruited via social media (e.g. Facebook, Instagram) and University newsletter (K-State Today) and indicated consent prior to participation in an online survey. Data were collected for demographics, anthropometrics, diabetes status, and PA behaviors. One-way ANOVAs, with Games-Howell post hoc tests were used to determine differences in aerobic activity and strength training between T1D, T2D, and ND participants. Results: Participants included 48 T1Ds, 24 T2Ds, and 240 NDs. Statistically significant differences existed for moderate aerobic PA between groups, ƒ(2, 304) = 3.9, p = 0.021, where T2D reported significantly fewer weekly minutes (109.2 ± 88.8) than ND (215.7 ± 186.5; p = 0.021); T1D’s weekly minutes (179.0 ± 171.7) were not significantly different. No significant vigorous PA differences were found between groups (p = 0.242; T1D = 66.3 ± 80; T2D = 41.7 ± 60.5; ND = 73.8 ± 94.8 min/week). Strength training days/week differed between groups, ƒ(2, 314) = 3.6, p = 0.028 with T1D (1.8 ± 2.0) reporting significantly more than T2D (0.7 ± 1.0; p = 0.024); ND’s days/week (1.5 ± 1.7) were not significantly different. Some diabetic participants felt moderately satisfied (34.2%) with their current exercise knowledge, while 62.3% wanted to gain more exercise knowledge. About 50% of the sample participated in active goal setting for their health and had current health goals, while 79.6% of the sample reported participating in exercise preparation behaviors and 85.6% participated in post-exercise care behaviors. The main forms of physical activity and exercise were walking and strength training. Conclusion: The hypothesis was partially supported in that participants with T1D reported significantly more strength training days/week than those with T2D, approaching the recommended 2 days/week. Of note, participants with T1D reported mean moderate PA greater than the recommended 150 min/week. A third of diabetic participants were satisfied with their current exercise knowledge while another 2/3 of diabetic participants wanted to gain more exercise knowledge. Current literature has reported that doctors who specialize in diabetes do not believe they have enough knowledge about the illness in relation to exercise to provide recommendations. Future studies should look deeper into PA knowledge not only of T1D and T2D, but of diabetic populations and their health care team members. Research should look into how individually and together this influences activity levels of diabetic populations.
Keywords: Diabetes; Obesity; T1D; T2D; Exercise; Physical activity